2017
DOI: 10.1001/jamaoncol.2017.1624
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based End-of-Life Care and Costs for Older Patients With Malignant Brain Tumors

Abstract: Approximately half of patients with a diagnosis of primary malignant brain tumor (PMBT) or secondary malignant brain tumor (SMBT) are older than 65 years and experience disproportionate mortality and symptom burden. End-of-life care for patients with terminal cancer is often aggressive, costly, and discordant with patient preferences. 1 However, a lack of knowledge remains about patterns of end-of-life care for the growing population of elderly people with a malignant brain tumor. This study compares hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Total Medicare expenditure in the final 30 days life was previously reported and was similar between patients with PMBT and SMBT ($8592 vs $9964, P = 0.75; Table 2). 27 Sensitivity analyses that included the dual-coded cohort provided similar results for total Medicare expenditures. In the multivariable model, hospice…”
Section: Medicare Expendituresmentioning
confidence: 83%
See 2 more Smart Citations
“…Total Medicare expenditure in the final 30 days life was previously reported and was similar between patients with PMBT and SMBT ($8592 vs $9964, P = 0.75; Table 2). 27 Sensitivity analyses that included the dual-coded cohort provided similar results for total Medicare expenditures. In the multivariable model, hospice…”
Section: Medicare Expendituresmentioning
confidence: 83%
“…In our previous study, we reported that SMBT patients were more likely than PMBT patients to be hospitalized in the final month of life (50% vs 42%, P = 0.009), and hospitalizations were associated with a significant increase in Medicare expenditures. 27 The transition to hospice in SMBT patients may be more likely to occur following hospitalizations, which would curtail any cost savings potentially associated with hospice in that population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing hospice utilization and reducing hospital deaths will reduce healthcare costs. One analysis found that hospice-based care in primary and metastatic brain tumor patients decreased Medicare costs by as much as $12,138 per patient whereas hospital-based care increased Medicare costs by as much $16,303 [41]. Future directions include prospective projects studying the implementation of standardized surveys and other tools to facilitate early, end-of-life discussion between providers, patients with brain tumors, and families, with a particular focus on at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor We read with interest the report by Dover and colleagues regarding the costs of end-of-life care for older adults with malignant primary and secondary brain tumors. To be honest, we expected the numbers to be worse.…”
mentioning
confidence: 99%